Analytical validation and cross-validation of an NFAT-regulated gene expression assay for pharmacodynamic monitoring of therapy with calcineurin inhibitors - Abdel-Kahaar, Emaad; Giese, Thomas; Sommerer, Claudia (Therapeutic drug monitoring, 2016)
Background: Analysis of residual gene expression of the nuclear factor of activated T cell (NFAT)-regulated genes has been developed as a pharmacodynamic biomarker to monitor therapy with calcineurin inhibitors. The availability of commercial primer sets (Search-LC) and the well-established assay protocol makes this biomarker a promising candidate to be used clinically in different laboratories. However, implementation of the method in routine practice requires analytical robustness and comparable results across laboratories. Therefore, a protocol originally established at the Institute of Immunology, Heidelberg was verified at the Institute of Laboratory Medicine, Klinikum Stuttgart, and a comparison study was conducted between the 2 laboratories. Methods: For the analytical verification, whole blood samples of healthy individuals were incubated with tacrolimus in vitro. Linearity, imprecision, and limit of quantification, as well as sample stability, were investigated. For interlaboratory comparison, samples of patients under cyclosporine A therapy were analyzed in Heidelberg and then reanalyzed in Stuttgart within 24 hours. Results: Tacrolimus (6.25-50 mcg/L) decreased the expression of NFAT-regulated genes in vitro dose dependently (15%-89%). Within- and between-assay coefficient of variations (n = 6 each) were <17%. The limit of quantification was <200 cDNA copies for each of the interleukin-2, interferon-γ, and granulocyte-macrophage colony-stimulating factor genes. Samples were stable for 24 hours. Interlaboratory comparison using patient samples correlated well (r = 0.951) but showed an inconsistent bias depending on the magnitude of residual gene expression.Conclusions: The assay can be set up with a satisfactory analytical performance in a routine molecular biological laboratory and shows comparable results between laboratories. The reproducibility of the NFAT-regulated gene expression assay across laboratories can facilitate the implementation of this assay for pharmacodynamic routine monitoring of calcineurin inhibitors in different centers.